106k views
4 votes
F(x) = 2x2 - 5x-3

8(x) = x2 + 6x-1
What is h(x) if h(x) = g(x)-f(x)?
A. h(x) = -12 + 11x + 2
B. h(x) = x2 - 11x-2
C. h(x) = -x2 + x - 4
D. h(x) = 3r2 + x - 4
E. h(x) = x2 +x+2

User Emelia
by
4.8k points

1 Answer

4 votes


(x^(2) + 6x - 1) - (2x^(2) - 5x - 3)


x^(2) + 6x - 1 - 2x^(2) + 5x + 3


- x^(2) + 11x + 2

So the answer is - x²+11x+2

User Noah Jacobson
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.